Endothelial α(1)-adrenoceptors regulate neo-angiogenesis - Ciccarelli, M (Nature Publishing Group, 2007)
BACKGROUND AND PURPOSE: Intact endothelium plays a pivotal role in post-ischaemic angiogenesis. It is a phenomenon finely tuned by activation and inhibition of several endothelial receptors. The presence of α(1)-adrenoceptors on the endothelium suggests that these receptors may participate in regenerative phenomena by regulating the responses of endothelial cells involved in neo-angiogenesis. EXPERIMENTAL APPROACH: We evaluated the expression of the subtypes of the α(1)-adrenoceptor in isolated endothelial cells harvested from Wistar-Kyoto (WKY) rats. We explored the possibility these α(1)-adrenoceptors may influence the pro-angiogenic phenotype of endothelial cells in vitro. In vivo, we used a model of hindlimb ischaemia in WKY rats, to assess the effects of α(1) adrenoceptor agonist or antagonist on angiogenesis in the ischaemic hindlimb by laser Doppler blood flow measurements, digital angiographies, hindlimb perfusion with dyed beads and histological evaluation. KEY RESULTS: In vitro, pharmacological antagonism of α(1)-adrenoceptors in endothelial cells from WKY rats by doxazosin enhanced, while stimulation of these adrenoceptors with phenylephrine, inhibited endothelial cell proliferation and DNA synthesis, ERK and retinoblastoma protein (Rb) phosphorylation, cell migration and tubule formation. In vivo, we found increased α(1)-adrenoceptor density in the ischaemic hindlimb, compared to non-ischaemic hindlimb, suggesting an enhanced α(1)-adrenoceptor tone in the ischaemic tissue. Treatment with doxazosin (0.06 mg kg(−1) day(−1) for 14 days) did not alter systemic blood pressure but enhanced neo-angiogenesis in the ischaemic hindlimb, as measured by all our assays. CONCLUSIONS: Our findings support the hypothesis that the α(1)-adrenoceptors in endothelial cells provide a negative regulation of angiogenesis.